PENGARUH EARNING PER SHARE DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR KABEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Rohma, - Sitti (EKONOMIA, 2019)
Sitti rohma: Influence Earning Per Share and Return On Equity To Price Stock on company sub sector manufacturing cables listed in Indonesia Stock Exchange Period 2012-2016 d church service guidance Mr H. Eddy Soegiarto K and Mrs Ivana Nina Esterlin Barus . Companies manufacturing sub sector cable is wrong one company manufacturing that becomes spotlight due to many project government through PT company State Electricity (PLN) where product cable many needed , with thereby issuers cable record growth profit clean enough significant.Research this aim for knowing influences : 1.) Earning Per Share to Price Stock 2.) Return On Equity to Price Shares . 3.) Earning Per Share and Return On Equity in together take effect significant . Data used on research this is secondary data in the form of report finance company sub sector manufacturing cable in 2012-2016 obtained on the official website of Indonesia Stock Exchange is www.idx.co.id.The method used in the research this is method descriptive . Of the 6 populations company sub sector manufacturing cable , obtained 6 companies samples that meet criteria testing . So that the amount of data to be analyzed numbered 30. Before do technique data analysis , especially first do test assumption classic . Testing statistics with use test multiple linear regression with do t test and F test. Partial calculation results indicate that Earning Per Share has a positive and significant effect on stock prices, with a significance value of 0.021 <0.05; partially Return On Equity does not affect the stock price, with a significance value of 0.071> 0.05; then the results of the study simultaneously show that Earning Per Share and Return On Equity have a positive and significant effect on stock prices, with a significance value of 0.000 <0.05.